2012
DOI: 10.1111/j.1477-2574.2012.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of remnant to total liver volume or remnant to body weight: which one is more predictive on donor outcomes?

Abstract: Remnant volume in a right lobe living donor hepatectomy has adverse effects on donor outcomes when RLV/TLV is ≤30% independent from the rate of RLV/BWR with a cut-off point of 0.6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 31 publications
(39 reference statements)
0
40
0
Order By: Relevance
“…Although a RV/TLV of at least 30%-35% is usually required to avoid small-for-size syndrome (SFSS) [1,4,8] , successful outcomes with RV/TLV < 30% have been reported in the setting of optimal liver quality [6,7,11,24] . Inclusion of the MHV with right grafts, which has been reported to optimize graft function [1,4,7,25] but to potentially impair remnant recovery [1,[26][27][28] , has both …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although a RV/TLV of at least 30%-35% is usually required to avoid small-for-size syndrome (SFSS) [1,4,8] , successful outcomes with RV/TLV < 30% have been reported in the setting of optimal liver quality [6,7,11,24] . Inclusion of the MHV with right grafts, which has been reported to optimize graft function [1,4,7,25] but to potentially impair remnant recovery [1,[26][27][28] , has both …”
Section: Discussionmentioning
confidence: 99%
“…Yaprak et al [11] had observed that RV/TLV ≤ 30% impacted donor outcome (especially postoperative hyperbilirubinemia and major complications) irrespective of donor RVBWR (< 0.6 or > 0.6). In their experience, RVBWR < 0.6 significantly affected liver function but not donor morbidity.…”
Section: Table 4 Middle Hepatic Vein Management In Small-for-size -Rementioning
confidence: 99%
See 3 more Smart Citations